Is pathogen prediction possible? - Arturo Casadevall (PLoS Biology)
As humanity comes into contact with new microbes, there is a need to identify which might be future pathogenic threats. Host-microbe interactions manifest emergent properties and chaotic dynamics, posing limits on prediction. However, probabilistic predictions are possible.